(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article delves into methods to enhance product manufacturing efficiency by refining the working parts of sorting robot manipulators in industrial processes. It highlights the role of robotic technologies, particularly manipulators, in boosting both efficiency and product quality in manufacturing. The study investigates key technological attributes of these robot manipulators, exploring ways to augment their operational performance and precision.